Drug Resistance Strategies and Substance Use among Adolescents in Monterrey, Mexico - Kulis, Stephen (2008)
This study examined drug resistance strategies and substance use among adolescents from Monterrey, Mexico. The focus was strategies that U.S. adolescents use most often to resist using substances, including refuse (saying no), explain (declining with an explanation), avoid (staying away from situations where drugs are offered), and leave (exiting situations where drugs are offered). Using self-administered questionnaire data from a convenience sample of 327 Mexican students enrolled at two secondary schools (preparatorias), we tested whether frequent use of particular drug resistance strategies predicted actual substance use. Multiple regression results showed that different strategies were effective for different substances, that some effects were mediated by number of offers received, and that certain effects were stronger for females than for males. Students using the refuse strategy reported less cigarette use and less binge drinking; those using the avoid strategy reported less alcohol and cigarette use; and those using the leave strategy reported less binge drinking and, for females only, less marijuana use. Use of the explain strategy was not significantly related to substance use after controlling for use of other strategies. Findings are discussed in terms of Mexican cultural values and their implications for the design of prevention programs for Mexican youth.